Replicating Schwardmann, Tripodi and van der Weele (AER 2022) - Roberto Brunetti; Alistair Cameron; Yao Kpegli; Jona Krutaj; Sudipta Sarangi (Institute for Replication (I4R), 2024)
Schwardmann et al. (2022) provide evidence from real-world debating competitions, that being randomly assigned to, and arguing for a given motion, increases one's own beliefs in the merit of the motion, and increases beliefs that factual statements in support of the motion, are correct. We conduct a robustness replication, focused on three main tests: i) Are results robust to the inclusion of controls for baseline beliefs via a differencesin-differences specification? ii) As error terms are plausibly correlated across outcome variables, are results robust to addressing this dependence through seemingly unrelated regression? iii) Whether results are robust to inclusion of team-level fixed effects? All findings of the paper are robust to these tests, and to a suite of other robustness exercises. We close our comment with a discussion of possible extensions which indicate potential heterogeneity in self-persuasion by gender, and by side of the debate.
Keywords: C93; D12; D72; D83; D91; I23; 330; Replication; confidence; beliefs; persuasion